The year in cardiovascular medicine 2020: arrhythmias. (3rd January 2021) - Crijns, Harry J G M; Prinzen, Frits; Lambiase, Pier D; Sanders, Prashanthan; Brugada, Josep
Graphical Abstract: Abstract: Summary of the progress in arrhythmias in 2020. RACE4 and ALL-IN indicated that integrated nurse-led care improves outcomes in AF patients. 3, 4 The same was reported for early rhythm control therapy 15 and cryoablation as initial AF treatment. 25, 26 Subcutaneous ICD was non-inferior to classical transvenous ICD therapy in PRAETORIAN. 54 One mechanistic study showed that autoantibodies against misexpressed actin, keratin, and connexin-43 proteins create a blood-borne biomarker profile enhancing diagnosis of Brugada syndrome. 50 Another mechanistic study indicated that transseptal LV pacing yields similar improvement in contractility as His bundle pacing whilst being more easy to execute. 44 In PRE-DETERMINE a simple-to-use ECG risk score improved risk prediction in patients with ischemic heart disease possibly enhancing appropriate ICD therapy in high risk patients. 58